The effects of chronic administration of mitragynine on cortical oscillations in rats - Doraisamy, Thilageswary a/p (2022)
Mitragynine is the significant alkaloid extracted from the leaves of M. speciosa (Kratom). The leaves have been extensively used to relieve pain as well as to aid in opioid withdrawal symptoms. Previous studies have recorded that drug do affect cognitive mechanisms in human yet the debate over the potential side effects of the drug which includes addiction risk and cognitive decline is still ongoing and also its underlying neural activity remains unclear. Thus, this study was designed to investigate the changes in brain spectral power and theta coherence after repeated exposure to mitragynine in freely moving rats. Male Sprague-Dawley rats was implanted with electrodes on right and left frontal cortex, hippocampal cornu ammonis (CA1), subiculum and sensory cortex for wireless EEG recording. Mitragynine (1, 5, and 10 mg/kg) was administered for 28 days, and EEG activity was recorded on day 7,14,21 and 28. The readings was transmitted to receiver and analyzed for different frequency range, delta (0.1-4Hz), theta (4-7Hz), alpha (7-13Hz) and beta (13-30Hz). The results have demonstrated frequency specific changes in spectral power occurring selectively in both cortical and hippocampal regions. In cortical regions, a general increase in beta power with collateral reduction in alpha power is seen as novel effects of mitragynine, while a reduction in delta power is appreciated in both cortical and hippocampal regions. Mitragynine induced reduction in theta coherance (4-7Hz) was seen as disruptions in functional connectivity between left frontal cortex and sensory cortex. It can be concluded that, these findings show mitragynine induced frequency specific changes in cortical neural oscillatory activity and suppressed theta coherence could potentially impact cognitive functioning.